Russian Foreign Policy : Balance Sheet 2019 - Cheang, Chris (2020)
As a new decade dawns, Russian foreign policy can boast some successes, mainly in Europe, the Middle East and Africa. However, apart from China, Moscow’s ties with the Asia-Pacific region are below par even though there is considerable potential for a stronger relationship.